Transformasi Politik: Peran Partai Politik dalam Meningkatkan Pendidikan dan Kesadaran Pluralisme di Pemilu Kota Kediri Tahun 2019 - Siti Amanah; Tatik Imadatus Sa’adati (JOM, 2021)
This study investigates the efforts made by political parties to enhance political literacy and promote pluralism in society, while also examining the facilitating and inhibiting factors involved. Employing a qualitative descriptive research approach, the study conducts interviews with relevant stakeholders across various political parties. Both primary and secondary data are gathered through methods including observation, in-depth interviews, and document analysis, and analyzed using the Miles and Huberman interactive model. The findings reveal that political parties assume diverse roles in advancing political education and pluralism, serving as channels for communication, platforms for socialization, avenues for recruitment, and agents for conflict resolution. Additionally, the General Election Commission (KPU) receives commendation for its effective performance, demonstrated by the successful execution of election processes in Kediri City with minimal disruptions and high public participation. The KPU's success is attributed to factors such as adequate funding, innovative socialization initiatives, collaborative relationships with stakeholders, governmental bodies, and religious leaders, as well as financial support from the Indonesian Democratic Party of Struggle (PDI-P) and its affiliated factions. However, the Democratic Party faces challenges due to limited financial resources, which hinder its efforts in political education.